Targeting the Human T-Cell Inducible COStimulator Molecule with a Monoclonal Antibody Prevents Graft-vs-Host Disease and Preserves Graft vs Leukemia in a Xenograft Murine Model - Burlion, Aude; Brunel, Simon; Petit, Nicolas Y.; Olive, Daniel; Marodon, Gilles (Frontiers in Immunology, 2017)
Background: Graft-versus host disease (GVHD) is a major complication of allogenic bone marrow transplantation (BMT). Targeting costimulatory molecules with antagonist antibodies could dampen the excessive immune response that occurs, while preserving the beneficial graft-versus-leukemia (GVL) of the allogeneic response. Previous studies using a mouse model of GVHD have shown that targeting the T cell inducible costimulatory (ICOS, CD278) receptor is beneficial but it is unclear whether the same applies to human cells. Methods: Here, we assessed whether a monoclonal antibody (mAb) to human ICOS was able to antagonize the costimulatory signal delivered in vivo to human T cells. To test this hypothesis, we used a xenogeneic model of GVHD where human PBMCs were adoptively transferred in immunocompromised NOD.SCID.gc-null mice (NSG). Results: In this model, control mice invariably lost weight and died by day 50. In contrast, 65% of the mice receiving a single injection of the anti-hICOS mAb survived beyond 100 days. Moreover, a significant improvement in survival was obtained in a curative xeno-GVHD setting. Mechanistically, administration of the anti-hICOS mAb was associated with a strong reduction in perivascular infiltrates in liver and lungs, and reduction in frequencies and numbers of human T cells in the spleen. In addition, the mAb prevented T cell expansion in the blood during xeno-GVHD. Importantly, GVHD-protected mice retained the ability to control the P815 mastocytoma cell line, mimicking GVL in humans. Conclusion: A monoclonal antibody targeting human ICOS alleviated GVHD without impairing GVL in a xenograft murine model. Thus, ICOS represents a promising target in the management of bone marrow transplantation, preventing GVHD while preserving GVL.